Pengaruh Harga dan Kualitas Produk Terhadap Keputusan Pembelian Sepatu Futsal Nike di Toko Venus Singaraja - I Putu Yuda Pranata; Ni Luh Wayan Sayang Telagawathi (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2021)
This study aims to examine the effect of: (1) price on purchasing decision, (2) product quality on purchasing decision, (3) price on product quality and (4) price on purchasing decision for Nike futsal shoes at Toko Venus Singaraja. The research design used in this research is causal quantitative. The objects of this research were price, product quality and purchase decisions. The research subjects were consumers who purchased Nike futsal shoes at Toko Venus Singaraja with a sample of 100 people. Data collected by questionnaire method. The analysis technique is used by path analysis. The results showed that: (1) price has a positive and significant effect on purchasing decision, (2) product quality has a positive and significant effect on purchasing decision, (3) price has a positive and significant effect on product quality and (4) price has a positive and significant effect on purchasing decision Nike futsal shoes at Toko Venus Singaraja.